Exploring patients' perspectives of gestational diabetes mellitus screening and counselling in Ontario: A grounded theory study. (18th January 2023) - Ruby, Emma; McDonald, Sarah D.; Berger, Howard; Melamed, Nir; Li, Jenifer; Darling, Elizabeth K.; Barrett, Jon; G. Ray, Joel; Geary, Michael; Murray‐Davis, Beth; ,
Abstract: Introduction: Gestational diabetes mellitus (GDM) is associated with adverse perinatal outcomes. Approaches to screening for GDM continue to evolve, introducing potential variability of care. This study explored the impact of these variations on GDM counselling and screening from the perspectives of pregnant individuals. Methods: Following a Corbin and Strauss approach to qualitative, grounded theory we recruited 28 individuals from three cities in Ontario, Canada who had a singleton pregnancy under the care of either a midwife, family physician or obstetrician. Convenience and purposive sampling techniques were used. Semi‐structured telephone interviews were conducted and transcribed verbatim between March and December 2020. Transcripts were analysed inductively resulting in codes, categories and themes. Results: Three themes were derived from the data about GDM screening and counselling: 'informing oneself', 'deciding' and 'screening'. All participants, regardless of geographical region, or antenatal care provider, moved through these three steps during the GDM counselling and screening process. Differences in counselling approaches between pregnancy care providers were noted throughout the 'informing' and 'deciding' stages of care. Factors influencing these differences included communication, healthcare autonomy and patient motivation to engage with health services. No differences were noted within care provider groups across the three geographic regions. Participant experiences of GDM screening were influenced by logistical challenges and personal preferences towards testing. Conclusion: Informing oneself about GDM may be a crucial step for facilitating decision‐making and screening uptake, with an emphasis on information provision to facilitate patient autonomy and motivation. Patient or Public Contribution: Participants of our study included patients and service users. Participants were actively involved in the study design due to the qualitative, patient‐centred nature of the research methods employed. Analysis of results was structured according to the emergent themes of the data which were grounded in patient perspectives and experiences.